2014
DOI: 10.21307/sjcapp-2015-013
|View full text |Cite
|
Sign up to set email alerts
|

Familiality of Quantitative Autism Traits

Abstract: Background: Autistic traits exist along a continuum that extends into social functioning in the general population, and they aggregate in the family members of children with autism spectrum disorder (ASD). Quantitative measures are therefore essential when investigating the patterns of familiality of these traits. Prior studies have suggested differential inheritance patterns of autistic traits that depend on the cognitive level of the child with ASD as well as the family type. Objective: Our goal was to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The severity of impairments typical for autism varies considerably within the spectrum. Moreover, it has been shown that difficulties and characteristics similar to those found in individuals with ASD diagnosis, so called "autistic traits", may be present in their close relatives (Duvekot, van der Ende, Constantino, Verhulst, & Greaves-Lord, 2016;Jussila et al, 2015;Pisula & Ziegart-Sadowska, 2015) and in the general population (e.g. Baron-Cohen, Wheelwright, Skinner, Martin, & Clubley, 2001;Ruzich et al, 2015).…”
Section: Determinants Of Life History Strategies Adopted In Our Studymentioning
confidence: 99%
“…The severity of impairments typical for autism varies considerably within the spectrum. Moreover, it has been shown that difficulties and characteristics similar to those found in individuals with ASD diagnosis, so called "autistic traits", may be present in their close relatives (Duvekot, van der Ende, Constantino, Verhulst, & Greaves-Lord, 2016;Jussila et al, 2015;Pisula & Ziegart-Sadowska, 2015) and in the general population (e.g. Baron-Cohen, Wheelwright, Skinner, Martin, & Clubley, 2001;Ruzich et al, 2015).…”
Section: Determinants Of Life History Strategies Adopted In Our Studymentioning
confidence: 99%